# If the ${m^{th}}$ term of an A.P be $\dfrac{1}{n}$ and ${n^{th}}$ term be $\dfrac{1}{m}$ , then show that its ${(mn)^{th}}$ term is 1.

Last updated date: 26th Mar 2023

•

Total views: 305.4k

•

Views today: 5.83k

Answer

Verified

305.4k+ views

Hint: Here, we will use the Arithmetic Progression Concept and the ${n^{th}}$term formulae i.e..,${T_n} = a + (n - 1)d$.

Complete step-by-step answer:

Given,

The ${m^{th}}$term of an A.P is $\dfrac{1}{n}$ and ${n^{th}}$term is $\dfrac{1}{m}$

Now, let us consider ‘a’ be the first term and‘d’ is the common difference of an A.P.As, we know that the ${n^{th}}$term of an A.P will be ${T_n} = a + (n - 1)d$.

Therefore, the ${m^{th}}$ term can be written as

$

\Rightarrow {m^{th}}term = \dfrac{1}{n} \\

\Rightarrow \dfrac{1}{n} = a + (m - 1)d \to (1) \\

$

Similarly, the ${n^{th}}$term is given as $\dfrac{1}{m}$, it can be written as

$

\Rightarrow {n^{th}}term = \dfrac{1}{m} \\

\Rightarrow \dfrac{1}{m} = a + (n - 1)d \to (2) \\

$

Let us subtract equation (2) from equation (1), we get

$

\Rightarrow \dfrac{1}{n} - \dfrac{1}{m} = a + (m - 1)d - a - (n - 1)d \\

\Rightarrow \dfrac{1}{n} - \dfrac{1}{m} = md - d - nd + d \\

\Rightarrow \dfrac{{m - n}}{{mn}} = (m - n)d \\

\Rightarrow \dfrac{1}{{mn}} = d \\

$

Hence, we obtained the value of d i.e.., $\dfrac{1}{{mn}}$.Now let us substitute the obtained value of d in equation (1), we get

$

(1) \Rightarrow \dfrac{1}{n} = a + (m - 1)d \\

\Rightarrow \dfrac{1}{n} = a + \dfrac{{(m - 1)}}{{mn}} \\

\Rightarrow \dfrac{1}{n} = a + \dfrac{1}{n} - \dfrac{1}{{mn}} \\

\Rightarrow \dfrac{1}{n} - \dfrac{1}{n} + \dfrac{1}{{mn}} = a \\

\Rightarrow \dfrac{1}{{mn}} = a \\

$

Hence, here also we got the value of ‘a’ as $\dfrac{1}{{mn}}$.Therefore, we can say

$a = d = \dfrac{1}{{mn}}$

Now, we need to find the ${(mn)^{th}}$term which is equal to ‘$a + (mn - 1)d$’.So substituting the obtained values of ‘a’ and d’ we get

$

\Rightarrow {(mn)^{th}}term = a + (mn - 1)d = \dfrac{1}{{mn}} + (mn - 1)(\dfrac{1}{{mn}}) = \dfrac{1}{{mn}} + 1 - \dfrac{1}{{mn}} = 1 \\

\Rightarrow {(mn)^{th}}term = 1 \\

$

Hence, we proved that the value of ${(mn)^{th}}$term is$1$.

Note: In an AP, d is the common difference of the consecutive terms i.e..,${t_3} - {t_2} = {t_2} - {t_1} = {t_n} - {t_{n - 1}} = d$.

Complete step-by-step answer:

Given,

The ${m^{th}}$term of an A.P is $\dfrac{1}{n}$ and ${n^{th}}$term is $\dfrac{1}{m}$

Now, let us consider ‘a’ be the first term and‘d’ is the common difference of an A.P.As, we know that the ${n^{th}}$term of an A.P will be ${T_n} = a + (n - 1)d$.

Therefore, the ${m^{th}}$ term can be written as

$

\Rightarrow {m^{th}}term = \dfrac{1}{n} \\

\Rightarrow \dfrac{1}{n} = a + (m - 1)d \to (1) \\

$

Similarly, the ${n^{th}}$term is given as $\dfrac{1}{m}$, it can be written as

$

\Rightarrow {n^{th}}term = \dfrac{1}{m} \\

\Rightarrow \dfrac{1}{m} = a + (n - 1)d \to (2) \\

$

Let us subtract equation (2) from equation (1), we get

$

\Rightarrow \dfrac{1}{n} - \dfrac{1}{m} = a + (m - 1)d - a - (n - 1)d \\

\Rightarrow \dfrac{1}{n} - \dfrac{1}{m} = md - d - nd + d \\

\Rightarrow \dfrac{{m - n}}{{mn}} = (m - n)d \\

\Rightarrow \dfrac{1}{{mn}} = d \\

$

Hence, we obtained the value of d i.e.., $\dfrac{1}{{mn}}$.Now let us substitute the obtained value of d in equation (1), we get

$

(1) \Rightarrow \dfrac{1}{n} = a + (m - 1)d \\

\Rightarrow \dfrac{1}{n} = a + \dfrac{{(m - 1)}}{{mn}} \\

\Rightarrow \dfrac{1}{n} = a + \dfrac{1}{n} - \dfrac{1}{{mn}} \\

\Rightarrow \dfrac{1}{n} - \dfrac{1}{n} + \dfrac{1}{{mn}} = a \\

\Rightarrow \dfrac{1}{{mn}} = a \\

$

Hence, here also we got the value of ‘a’ as $\dfrac{1}{{mn}}$.Therefore, we can say

$a = d = \dfrac{1}{{mn}}$

Now, we need to find the ${(mn)^{th}}$term which is equal to ‘$a + (mn - 1)d$’.So substituting the obtained values of ‘a’ and d’ we get

$

\Rightarrow {(mn)^{th}}term = a + (mn - 1)d = \dfrac{1}{{mn}} + (mn - 1)(\dfrac{1}{{mn}}) = \dfrac{1}{{mn}} + 1 - \dfrac{1}{{mn}} = 1 \\

\Rightarrow {(mn)^{th}}term = 1 \\

$

Hence, we proved that the value of ${(mn)^{th}}$term is$1$.

Note: In an AP, d is the common difference of the consecutive terms i.e..,${t_3} - {t_2} = {t_2} - {t_1} = {t_n} - {t_{n - 1}} = d$.

Recently Updated Pages

Calculate the entropy change involved in the conversion class 11 chemistry JEE_Main

The law formulated by Dr Nernst is A First law of thermodynamics class 11 chemistry JEE_Main

For the reaction at rm0rm0rmC and normal pressure A class 11 chemistry JEE_Main

An engine operating between rm15rm0rm0rmCand rm2rm5rm0rmC class 11 chemistry JEE_Main

For the reaction rm2Clg to rmCrmlrm2rmg the signs of class 11 chemistry JEE_Main

The enthalpy change for the transition of liquid water class 11 chemistry JEE_Main

Trending doubts

Difference Between Plant Cell and Animal Cell

Write an application to the principal requesting five class 10 english CBSE

Ray optics is valid when characteristic dimensions class 12 physics CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Write the 6 fundamental rights of India and explain in detail

Write a letter to the principal requesting him to grant class 10 english CBSE

List out three methods of soil conservation

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Write a letter to the Principal of your school to plead class 10 english CBSE